2010
DOI: 10.1002/ange.200905039
|View full text |Cite
|
Sign up to set email alerts
|

High‐Resolution Single‐Turnover Mapping Reveals Intraparticle Diffusion Limitation in Ti‐MCM‐41‐Catalyzed Epoxidation

Abstract: Katalyse in neuem Licht: Mithilfe hochauflösender Fluoreszenzmikroskopie gelang es erstmals, Transportphänomene und deren Rolle in der Katalyse auf Einzelpartikelebene zu kartieren. Der Thiele‐Modul konnte partikelweise in nur einem einzigen Experiment gemessen werden, und er beweist das Vorliegen von Diffusionsbeschränkungen bei der Ti‐MCM‐41‐katalysierten Epoxidierung eines fluoreszierenden Reportermoleküls (siehe Bild; TBHP=tert‐Butylhydroperoxid).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
81
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(85 citation statements)
references
References 47 publications
1
81
0
3
Order By: Relevance
“…[15] Ti-MCM-41 nanoparticles displayed higher conversions and initial reaction rates in the epoxidation of cyclohexene than Ti-MCM-41 with micrometric particle size, because the accessibility of the catalytic Ti species was enhanced in these Ti-MCM-41 nanoparticles. [17][18][19] These results indicate that porous titanosilicates in the form of nanoparticles have many benefits for catalytic applications in various selective oxidations over the corresponding large particles. An alternative way to improve the catalytic activity of TS-1 crystals in the epoxidation of large substrates is to increase the accessibility of the Ti sites by creating mesopores in the zeolitic structure.…”
Section: Introductionmentioning
confidence: 96%
“…[15] Ti-MCM-41 nanoparticles displayed higher conversions and initial reaction rates in the epoxidation of cyclohexene than Ti-MCM-41 with micrometric particle size, because the accessibility of the catalytic Ti species was enhanced in these Ti-MCM-41 nanoparticles. [17][18][19] These results indicate that porous titanosilicates in the form of nanoparticles have many benefits for catalytic applications in various selective oxidations over the corresponding large particles. An alternative way to improve the catalytic activity of TS-1 crystals in the epoxidation of large substrates is to increase the accessibility of the Ti sites by creating mesopores in the zeolitic structure.…”
Section: Introductionmentioning
confidence: 96%
“…Sels and co-workers confirmed that the particle size of Ticontaining mesoporous silica materials affect their catalyst activity for olefin oxidations due to the limitation of intraparticle diffusion, and suggested that only in submicrometer particles size would the Ti sites be fully used for catalysis [15]. Pescarmona proved that Ti-MCM-41 nano-particle shows higher catalyst activity than Ti-MCM-41 large particle [14].…”
Section: Introductionmentioning
confidence: 92%
“…Analogous studies revealed the influence of the pore dimension on diffusion phenomena during catalyst operation [107,108]. In recent years, high-resolution spectroscopic methods have reached the spatiotemporal resolution required to detect single turnover events, at the nanoscale, during the catalytic action of porous catalysts [84,109]. Coupling of these imaging techniques with deliberate morphological control of ordered mesoporous supports or catalysts, for example, by tuning pore size and length [110,111], is anticipated to help in elucidating the relative kinetic relevance of intra-pore mass transport and surface reaction phenomena, and thereby guide the design of more efficient catalysts.…”
Section: Recent Examples For the Use Of 3d Model Systems To Guide Catmentioning
confidence: 99%